Systematic Scoping on Point-of-care Monitoring of Direct Oral Anticoagulants in Patients with Non-valvular Atrial Fibrillation: Current Status and Future Perspectives in Malaysia - Shirley Siang Ning, Tan; Edmund Ui Hang, Sim; Lawrence, Anchah (Radcliffe Group Ltd., 2025)
This review explores the use of point-of-care (POC) monitoring of direct oral anticoagulants (DOACs) in patients with non-valvular AF globally and in Malaysia. As patent protection measures for innovative medicines come to an end, and generic alternatives become available, we expect a greater uptake of DOACs than warfarin by patients due to cost advantages. However, the anticoagulation effect of DOACs has been shown to vary from patient to patient and is associated with thrombotic and bleeding risks. Despite the availability of laboratory technology, including at POC, that can monitor the pharmacological effects of DOACs, it has not achieved any substantial traction in clinical use to date. Future efforts should focus on establishing the therapeutic window or ‘sweet spot’ of DOAC therapy for the POC assays and ensuring adherence before implementation of POC monitoring. This is crucial for the tailoring of anticoagulation therapy, potentially reducing overall healthcare costs and improving patient health outcomes.